Lactobacilli displacement and Candida albicans inhibition on initial adhesion assays: a probiotic analysis - Robert Josue Rodríguez-Arias; Bryan Omar Guachi-Álvarez; Dominique Esther Montalvo-Vivero; António Machado (BMC Research Notes, 2022)
Abstract Objective This study evaluates the probiotic activity of three vaginal Lactobacillus gasseri (H59.2, IMAUFB014, and JCM1131) and one non-vaginal L. plantarum ATCC14917 against three Candida albicans (ATCC10231, candidiasis, and healthy vaginal microbiota). Displacement of lactobacilli and adhesion inhibition of C. albicans were evaluated on an abiotic surface through adhesion assays with different experimental settings (ES) through low (1.0E + 03 CFU/ml) and high (1.00E + 09 CFU/ml) levels of colonization. ES simulated dysbiosis (ES1 and ES4), candidiasis (ES2), and healthy vaginal microbiota (ES3). Results At ES2 and ES3, L. gasseri H59.2 showed discrepant inhibition values among C. albicans isolates (ES2: P = 0.008, ES3: P = 0.030; two‐way ANOVA). L. plantarum was only displaced by 23%, 31%, 54%, and 94% against low and high levels of C. albicans ATCC10231. L. plantarum was less displaced, when compared to L. gasseri strains (ES1: 61–84%, ES2: 82–96%, ES3: 83–95%, and ES4: 73–97%), showing multiple statistical differences (ES1: P =  < 0.001, ES2: P = 0.003, and ES3: P =  < 0.001; two‐way ANOVA). L. plantarum also showed a superior inhibition of C. albicans ATCC10231 in ES1 (81%) and ES2 (58%) when compared to L. gasseri strains (ES1: 27–73%, P < 0.001; and ES2:1–49%, P < 0.001; two‐way ANOVA).